Hsa_circ_0016760 exacerbates the malignant development of non‑small cell lung cancer by sponging miR‑145‑5p/FGF5 - Zhu, Zheng; Wu, Qiyong; Zhang, Ming; Tong, Jichun; Zhong, Bin; Yuan, Kai (Oncology reports, 2021)
Hsa_circ_0016760 expression has been reported to be increased in non‑small cell lung cancer (NSCLC). The present study was designed to explore the role and mechanism of hsa_circ_0016760 in regulating NSCLC progression. In total, 60NSCLC patients were followed‑up for 60 months after surgery. Hsa_circ_0016760 expression in tumor tissues and adjacent non‑tumor tissues of NSCLC patients was explored by reverse transcription quantitative polymerase chain reaction (RT‑qPCR). NSCLC cell proliferation was monitored by CCK‑8 assay and EdU experiment. Transwell assays were used for the detection of NSCLC cell migration and invasion. The target of hsa_circ_0016760 (or miR‑145‑5p) was validated by luciferase reporter gene assay and RNA immunoprecipitation experiment. A xenograft model was studied with nude mice. Immunohistochemical staining was applied for the detection of Ki67 expression in xenograft tumors. Hsa_circ_0016760/miR‑145‑5p/FGF5 expression in tissues and cells was investigated by RT‑qPCR and western blotting. Hsa_circ_0016760 was aberrantly upregulated in NSCLC, which was associated with poor prognosis of patients (P<0.05). Hsa_circ_0016760 silencing suppressed NSCLC cell proliferation, migration and invasion in vitro (P<0.01). Hsa_circ_0016760 facilitated FGF5 expression via sponging miR‑145‑5p. The miR‑145‑5p upregulation or FGF5 downregulation reversed the promoting effect of hsa_circ_0016760 on NSCLC cell proliferation, migration and invasion in vitro (P<0.01). In addition, hsa_circ_0016760 silencing inhibited tumor growth in vivo (P<0.01), and decreased Ki67 expression in xenograft tumors. In conclusion, hsa_circ_0016760 exacerbated the malignant development of NSCLC by sponging miR‑145‑5p/FGF5.